PERANAN ORANG TUA DALAM BIMBINGAN KONSELING SISWA - Mukh. Sihabudin (Jurnal Kependidikan, 2017)
Acting art of Parent for building character them children that very needed. The Parents more understand all things problem that to strike them children these days or future time. Its not to understand only but their must be conclude the wise stance to position them self between children’s life, and then can be give the good solution that convering the freshness for them existence. So the parents must be doing something attempts such as How acting part of parents to grow and to arouse children personality that proper with them ecpectation.Whatever must be undertaken to dig counseling potenty that possessed by parents,How parents attempts to be good concelour forward children.